An optimized thermal network model to evaluate the thermal behavior on motorized spindle considering lubricating oil and contact factors. (July 2022) - Su, Chuan; Chen, Weifang
During the operation of the high-speed motorized spindle, the heating of motorized spindle components can cause thermal deformations, which worsens the work performance and shortens the life expectancy of the motorized spindle. In response to the above behaviors, the thermal network model for the motorized spindle in this investigation was built in which the lubricating oil properties and contact characteristics were considered. Next, according to Kirchhoff's energy balance principle, the theoretical equations of steady-state temperature were established, and the temperature rise of the motorized spindle was obtained by Newton–Raphson method. Lastly, the influences of speed, cooling water flow rate, airflow rate, and other variables on the temperature were analyzed and verified by the experiment. The results show that the thermal network model including lubricating oil and contact factors can predict the temperature rise of motorized spindle accurately, which provides some references and suggestions in motorized spindle design.